Social Determinants of Gestational Weight Gain in an Obese, Low-Income Population - Ratan, Bani Maheshwari; Garbarino, Abigail Hook; Sellner, Allison Archer; Miao, Di; Hollier, Lisa Marie (American Journal of Perinatology, 2020)
Objective To examine how social support factors affect compliance with gestational weight gain (GWG) recommendations in an obese, low-income, predominantly minority population.Study Design A retrospective cohort of 772 pregnant women with body mass index > 30 was reviewed. Univariate and multinomial logistic regression analyses were used to compare GWG with pregnancy planning, relationship status, participation in group prenatal care, nutritional education, and demographic factors. Subgroup analysis was performed to determine if differences existed in entry into prenatal care.Results Planned nature of pregnancy, relationship status, nutritional education, and group prenatal care did not significantly affect GWG. Women with planned pregnancies and in group prenatal care had their first appointment during the first trimester at a higher rate than those with unplanned pregnancy and in traditional care, respectively. Regardless of timing of nutrition consult, GWG was not affected. Nulliparous patients and Class 1 obese patients were more likely to have excessive GWG.Conclusion Social support factors in this study did not individually affect compliance with GWG recommendations in a low-income, obese pregnant population, although some factors were associated with earlier entry to prenatal care. Multimodal, longitudinal programs are likely necessary to achieve increased compliance with GWG recommendations in this population.
Keywords: gestational weight gain; obesity; planned pregnancies; group prenatal care; nutritional counseling